Deep Learning and Indian Heritage - S.Charulatha, B; Rajaraman, Arun (International Journal of Engineering and Technology, 2018)
Deep learning is becoming increasingly necessary as data, information and web and mobile interaction are proliferating with form, type and volume of data becoming easy to store, retrieve and process. This necessity is felt not only in science and engineering but also in social and commercial internet activity. The paper explores some ideas of deep learning to process large data in the context of content extraction in a heterogeneous web page containing multi-lingual information, in the Indian context. This basis is used to explore how Indian heritage over several thousands of years, is able to maintain information and knowledge in certain areas through oral, palm leaf and stone-cut data forms. The paper extends the proposed method to some heritage data and concludes how complex from computing point of view to extract the knowledge and essence of some texts like Bhagavad Gita. Â